2016
DOI: 10.1186/s41124-016-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

A community- based hepatitis B linkage-to-care program: a case study on Asian Americans chronically infected with hepatitis B virus

Abstract: BackgroundHepatitis B is an important disease of ethnic disparity which affects Asian Americans and other minority populations disproportionately. Despite the high prevalence of hepatitis B in Asian Americans, many of them remain unscreened and untreated. A majority of the individuals chronically infected with hepatitis B virus (HBV) are not linked to care, for instance, due to a lack of culturally competent programs. There are many serious barriers preventing linkage to care (LTC), including personal, socio-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…The PN offered a culturally and linguistically tailored navigator program in coordinating access to clinical care by providing the subjects with the available healthcare resources in the community. The PN initially assessed each subject to determine his or her background and needs, and subsequently communicated with the subjects to direct them to meet 37 The high linkage rate of 88% from the CHB group in the current study also supports the critical role of the PN program in facilitating the linkage.…”
Section: Role Of the Patient Navigator In Linkagementioning
confidence: 72%
“…The PN offered a culturally and linguistically tailored navigator program in coordinating access to clinical care by providing the subjects with the available healthcare resources in the community. The PN initially assessed each subject to determine his or her background and needs, and subsequently communicated with the subjects to direct them to meet 37 The high linkage rate of 88% from the CHB group in the current study also supports the critical role of the PN program in facilitating the linkage.…”
Section: Role Of the Patient Navigator In Linkagementioning
confidence: 72%
“…The continual monitoring and management of CHB patients are paramount in successful linkage in care of CHB. Although our study did not employ a control group, followed in the absence of a community campaign, the current and previous studies have demonstrated a significant lack of LTC in HBV infected patients [6, 9, 11, 12, 18]. For instance, it was estimated that 40% of the HBV infected subjects screened in community settings were linked to care [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increasing health literacy may help improve patients’ understanding of the need for LTC, and that understanding will, in turn, lead to higher demand for access to care and thus for health insurance. Further, a patient navigator program, which has been shown to enhance access to care in hepatitis B [12, 29, 30], may be implemented to further facilitate LTC efforts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations